PENERAPAN MANAJEMEN SECURITY PADA MAHASISWA PSIKOLOGI YANG MENGALAMI AKADEMIK BURNOUT - Aisyah Nurfitriani; Edy Soesanto; Elen Nofita Sari; Wahyuning Tyas Permatasari (CV. Adiba Aisha Amira, 2023)
Academic Burnout is a condition or situation experienced by an individual where he feels tired which refers to psychological factors. This burnout is caused by the learning activities carried out which make the individual feel emotionally tired. Students who experience burnout will exhibit behavior that will cause delays in learning patterns. The behavior of these aspects given or shown by students needs to be controlled. Security Management is a security system or system of understanding how to prevent obstacles, disturbances and threats appropriately and effectively against the conditions being experienced. The method used in this research is a literature review which is used as a contact review, because literature helps the writer provide understanding and meaning of the writing that is being done. Researchers look for literature sources that help researchers uncover academic burnout and security management, then analyze and conduct discussions. The results of the analysis carried out by the author on how Security Management is applied to students who experience academic burnout, namely currently students who experience academic burnout are in the moderate category. Academic burnout arises from the existence of poor relationships between lecturers and students which can give rise to procrastinator behavior. , lack of appreciation, work overload, and injustice. Academic burnout can be overcome with social support, especially from family, students must have resilience, and students must also implement stress management. The conclusion is that students who experience academic burnout are in the moderate category. Students can apply stress management, resilience and get social support.